Improved growth and survival of Catla catla larvae using cultured microalgae and zooplankton as initial feed - Most. Sanjida Sultana; Md. Mahfuzul Haque; Md. Yeamin Hossain; Md Kowshik Ahmed; Mohammad Ariful Islam Sumon; Most. Suraiya Nisha Akhi; Saleha Khan (Aquaculture Reports)
Microalgae and zooplankton offer a multitude of potential applications as essential nutritional sources during the early developmental stages of various fish, mollusks, and crustaceans. This study assessed the efficacy of the microalgae, specifically Chlorella sp. and Desmodesmus sp., as well as cultured zooplankton such as copepods and cladocerans as initial feed in improvement of the growth and survival rate of the major carp Catla catla larvae. Newly hatched 4-day-old C. catla larvae were reared over the course of 40 days using six distinct experimental diets. The diets included Chlorella sp. in T1, Desmodesmus sp. in T2, cultured copepods and cladocerans in T3, combination of Chlorella sp. and cultured copepods and cladocerans in T4, combination of Desmodesmus sp. and cultured copepods and cladocerans in T5, and commercial powdered larval feed in T6. Significantly (P < 0.05) higher gain in length, gain in weight, percent length gain, percent weight gain, and specific growth rate were found in T3 followed by T4, T5, T1, T6 and T2. On the contrary, the highest percent survival rate was found in T4 (93.29 ± 0.38 %) followed by T5 (91.86 ± 0.90 %), T3 (84.75 ± 1.11 %), T1 (78.67 ± 0.74 %), T2 (73.01 ± 0.41 %), and T6 (67.07 ± 0.70 %). Biochemical investigations revealed that the different nutritional compositions in each feed significantly impacted on the crude protein and lipid content in the carcass of the C. catla larvae. The study conclusively demonstrated that the cultured zooplankton, either as sole feed or in combination with either of Chlorella sp. or Desmodesmus sp. considerably enhanced both the survival rate and the growth of the C. catla larvae in comparison to the microalgae alone and the commercial formulated powdered larval fish feed.